Arctic Human Development Report (2009)
The Arctic Human Development Report is the first comprehensive assessment of human well-being covering the entire Arctic region. Based on contributions from some 90 scientists located in all the members of the Arctic Council and coordinated by a secretariat based at the Stefansson Arctic Institute in Akureyri, Iceland, the report offers a wide-ranging scientific assessment of achievements and challenges relating to human development in the Arctic.